2012
DOI: 10.1039/c2ob06931h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of donor–acceptor chromophores by the [2 + 2] cycloaddition of arylethynyl-2H-cyclohepta[b]furan-2-ones with 7,7,8,8-tetracyanoquinodimethane

Abstract: Arylethynyl-2H-cyclohepta [b]furan-2-ones reacted with 7,7,8, in a formal [2+2] cycloaddition reaction, followed by ring opening of the initially formed cyclobutene derivatives, to afford the corresponding dicyanoquinodimethane (DCNQ) chromophores in excellent yields. The intramolecular charge-transfer (ICT) interactions between the 2H-cyclohepta[b]furan-2-one 10 ring and DCNQ acceptor moiety were investigated by UV/Vis spectroscopy and theoretical calculations. The redox behavior of the novel DCNQ derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 76 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Te trathiafulvalene (TTF) and extended TTF derivatives showed as imilar activity to monothiophene.H eating to reflux in 1,2-dichloroethane was necessary for the reaction to proceed, and the TCBD products were obtained in moderate yields (Table 1, entries 8a nd 9). [26,27] In particular, azulene derivatives showed av ery high activity,similar to the p-N,N-dialkylanilino donors.Thus, as eries of linear and branched oligo(ethynylazulene)s were prepared as precursors and their TCBD products synthesized in very high yields (Table 1, entries 10 and 11). [26,27] In particular, azulene derivatives showed av ery high activity,similar to the p-N,N-dialkylanilino donors.Thus, as eries of linear and branched oligo(ethynylazulene)s were prepared as precursors and their TCBD products synthesized in very high yields (Table 1, entries 10 and 11).…”
Section: Electron Donors Activating the Alkyne Componentmentioning
confidence: 94%
See 1 more Smart Citation
“…Te trathiafulvalene (TTF) and extended TTF derivatives showed as imilar activity to monothiophene.H eating to reflux in 1,2-dichloroethane was necessary for the reaction to proceed, and the TCBD products were obtained in moderate yields (Table 1, entries 8a nd 9). [26,27] In particular, azulene derivatives showed av ery high activity,similar to the p-N,N-dialkylanilino donors.Thus, as eries of linear and branched oligo(ethynylazulene)s were prepared as precursors and their TCBD products synthesized in very high yields (Table 1, entries 10 and 11). [26,27] In particular, azulene derivatives showed av ery high activity,similar to the p-N,N-dialkylanilino donors.Thus, as eries of linear and branched oligo(ethynylazulene)s were prepared as precursors and their TCBD products synthesized in very high yields (Table 1, entries 10 and 11).…”
Section: Electron Donors Activating the Alkyne Componentmentioning
confidence: 94%
“…[24,25] Shoji et al found that alkynylated azulene and 2H-cyclohepta [b]furan-2-one derivatives are remarkably potent donors for CA-RE reactions. [26,27] In particular, azulene derivatives showed av ery high activity,similar to the p-N,N-dialkylanilino donors.Thus, as eries of linear and branched oligo(ethynylazulene)s were prepared as precursors and their TCBD products synthesized in very high yields (Table 1, entries 10 and 11). Spectroelectrochemical measurements suggested the potential of these new azulene derivatives for use as reversible electrochromophores.…”
Section: Electron Donors Activating the Alkyne Componentmentioning
confidence: 94%
“…Thus, we investigated the preparation of new TCBDs based on CHFs for the construction of multistage redox activec hromophores. The alkynes also reactedw ith TCNQ [58] and DDQ [59] to afford the corresponding addition products. Similar to TCBD derivatives with azulenyl substituents, CHF-substituted TCBDs 47-53 were obtained by the [2+ +2] CA-RE of the correspondinga lkynes with TCNE ( Figure 9).…”
Section: Heteroazulenylt Cbds With Aryl Substituentsmentioning
confidence: 99%
“…2 As an extension of this study, Diederich et al have reported the sequential [2 + 2] cycloaddition reaction of tetracycnoethylene (TCNE) and TTF with 25 dialkylamino-(DAA-) substituted electron-rich butadiynes yielding multivalent charge-transfer (CT) chromophores, tetracyanobutadiene (TCBD)/1,2-bis(1,3-dithiol-2-ylidene)ethane derivatives, that are capable of taking up an exceptional number of electrons under electrochemical conditions. 3 30 Azulene (C 10 H 8 ) has attracted the interest of many research groups owing to its unusual properties as well as its beautiful blue color.…”
Section: Introductionmentioning
confidence: 99%